Asian Americans’ Views of their Identities as Asians in Eleanor & Park: A Socio-Psychological Approach - Aulia Nur Afifah; Muh Arif Rokhman (Universitas Gadjah Mada, 2021)
This research analyzes how Asian American characters, Mindy Sheridan, Park Sheridan, and Josh Sheridan, in the novel Eleanor & Park view their identities as Asians. This research aims to understand how Asian American characters view their identities as Asians and what factors influence their views. The analysis of this research was conducted using the social psychology approach supported by Tajfel and Turner’s (2004) social identity theory and Atkinson, Morten, and Sue’s (1998) minority identity development model. This research shows that Asian American characters’ views of their identity as Asian are influenced by the values believed by the dominant group in their social environment.